Pengaruh Customer Value Dan Customer Relationship Terhadap Customer Loyalty Di Exsa English Course Bandung - Fransiska Subari (Business Administration Department - Universitas Katolik Parahyangan, 2010)
English has been known as the international language that will be needed to communicateworldwide. In the other hand, this language has been perceived as a difficultskill to learn. That will create a de-motivation condition upon several people to learnthis skill. In that condition, the English course service providers must carefully delivertheir programs to get people’s attention as well as their loyalty. In this case,the providers not only need to offer a good value of their programs but also a goodcustomer relationship. A research conducted in an English course institution that hasbeen established since 1971 discovered the effect of customer value and customerrelationship to their customer loyalty.Keywords: customer value, customer relationship, customer loyalty